2017
DOI: 10.1038/s41598-017-06372-z
|View full text |Cite
|
Sign up to set email alerts
|

The lipid peroxidation product 4-hydroxynonenal contributes to oxidative stress-mediated deterioration of the ageing oocyte

Abstract: An increase in intraovarian reactive oxygen species (ROS) has long been implicated in the decline in oocyte quality associated with maternal ageing. Oxidative stress (OS)-induced lipid peroxidation and the consequent generation of highly electrophilic aldehydes, such as 4-hydroxynonenal (4-HNE), represents a potential mechanism by which ROS can inflict damage in the ageing oocyte. In this study, we have established that aged oocytes are vulnerable to damage by 4-HNE resulting from increased cytosolic ROS produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 113 publications
(142 reference statements)
5
76
0
2
Order By: Relevance
“…Perhaps most intriguing was the observation that these phenotypic changes were positively correlated with 4-HNE modification of a subset of vulnerable oocyte proteins, including those of the tubulin family. Moreover, interventions designed to limit 4-HNE bioavailability, and thus reduce tubulin adduction, were able to ameliorate the deleterious effect of oxidative stress on oocyte quality (29). Such findings are in accord with the key role of the microtubule network in supporting faithful meiotic completion, with defects in these cytoskeletal elements associated with elevated rates of oocyte aneuploidy (44,45).…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Perhaps most intriguing was the observation that these phenotypic changes were positively correlated with 4-HNE modification of a subset of vulnerable oocyte proteins, including those of the tubulin family. Moreover, interventions designed to limit 4-HNE bioavailability, and thus reduce tubulin adduction, were able to ameliorate the deleterious effect of oxidative stress on oocyte quality (29). Such findings are in accord with the key role of the microtubule network in supporting faithful meiotic completion, with defects in these cytoskeletal elements associated with elevated rates of oocyte aneuploidy (44,45).…”
supporting
confidence: 56%
“…Despite the pervasive impact of oxidative stress on oocyte quality, the mechanisms by which this insult inflicts such damage are still being actively debated. In this context, recent studies have identified elevated production of lipid aldehydes accompanying the induction of oxidative stress in oocytes and have shown that these highly reactive entities contribute, in part, to the loss of oocyte quality (28,29). This situation mirrors the response of somatic cells in which the induction of oxidative stress precipitates the peroxidation and breakdown of membrane lipids (including glycolipids, phospholipids, and cholesterol) (30 -32), with -6 polyunsaturated fatty acids such as arachidonic and linoleic acids being particularly susceptible (33,34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate if melatonin regulated CME by its antioxidative mechanism, H 2 O 2 was supplemented in the IVM culture solution at a final concentration of 35 μM, as referenced from murine oocytes . GV‐stage oocytes were divided into three IVM groups—the control group, 35 μM H 2 O 2 alone (the H group), or 35 μM H 2 O 2 along with 10 −11 M melatonin (the H + M group).…”
Section: Methodsmentioning
confidence: 99%
“…To demonstrate if melatonin regulated CME by its antioxidative mechanism, H 2 O 2 was supplemented in the IVM culture solution at a final concentration of 35 μM, as referenced from murine oocytes. 33…”
Section: H 2 O 2 Treatmentmentioning
confidence: 99%